DETERMINAN MANAJEMEN PAJAK PERUSAHAAN: UKURAN PERUSAHAAN, PENDANAAN UTANG, PROFITABILITAS, INTENSITAS ASET TETAP DAN MEKANISME TATA KELOLA - Umi Pratiwi (JURNAL AKUNTANSI DAN AUDITING, 2019)
This study aims to examine financial (firm size, leverage, profitability, capital intensity) and non-financial factors (independent commissioners, audit committees, managerial ownership, institutional ownership as corporate governance mechanisms) on corporate tax management in manufacturing firms listed on the Indonesian Stock Exchange 2016-2017. The population of this research is 151 manufacturing firms. The sample measurement method is purposive sampling to obtain 36 sample firms with 72 observations according to the observation period. Data is analyzed with multiple regression analysis methods. The results of this research indicate that profitability, capital intensity, independent commissioners and audit committees influence the corporate tax management partially.  Meanwhile, firm size, leverage, managerial and institutional ownership have no influence on tax management. In general, corporate tax management can be indicated from the financial and non-financial factors.